Cálculo de potenciais de redução em meio aprótico (dmf) de adutos da reação de Morita-Baylis-Hillman com potencialidades biológicas anti-leishmania - Silva, Amauri Francisco da (2015)
Nitroaromatic compounds derived from Morita-Baylis-Hillman reaction (RMBH) have been tested in the treatment of most neglected diseases such as malaria, Chagas disease and leishmaniasis. An important experimental observation is the relation between biological activity (measured by IC50) and reduction potential of these compounds (estimated by the cathodic and anodic peak potentials determined by electroanalytical techniques), the latter directly connected to the reduction of the nitro group (-NO2 ). For this reason, electrochemical methods have been used in order to mimic the enzymatic bioreduction of these compounds, as reported by Vasconcellos et al. (J. Braz. Chem. Soc. 23:894, 2012). The objective of this work was to develop a computational protocol to predict the reduction potential in aprotic media to support the molecular modeling of new compounds with desired pharmacological activity. The developed direct protocol (for aprotic solvents) consists of performing DFT calculations with B98, PBE1PBE or M06-2X functionals with 6-31+G(d,p) basis set and C-PCM solvation method (with standard cavitation method UFF/VdW). The results show that it is possible to predict the experimental variation of the reduction potential of at least 70 % of confidence (in a range of experimental data of only 140 mV) with absolute average errors less than 45 mV (much less than the experimental uncertainty of the absolute reaction potential of hydrogen electrode, approximately 400 mV) and standard deviation of about 35 mV (inferior to 1,0 kcal/mol). The application of direct protocol for a series of 65 uncorrelated molecules, whose reduction potentials vary in a range of more than 6 V, provided a model with more than 99% of predictive power. From the application of the protocol to a series of 40 molecules, for which experimental results are not available, it was possible to predict that some of these structures may have more favorable potentials to bioreduction process than the systems used in the calibration step, which makes them candidates for new drugs.